Pengaruh Dimensi Fraud Triangle dan Penyalahgunaan Teknologi Informasi Terhadap Academic Fraud: Studi Empiris pada Mahasiswa Akuntansi Universitas Negeri Padang - Faadhilah, Mia; Fauzihardani, Eka (Universitas Negeri Padang, 2025)
This research aims to empirically prove the influence of triangle fraud dimensions and misuse of information technology on academic fraud. This research was conducted on accounting students majoring in accounting class 2020 and 2021 at the Faculty of Economics and Business, Padang State University. Sampling was carried out using the proportional random sampling method. Data collection was carried out by distributing questionnaires via Google Form. The data analysis technique used to prove the truth of the hypothesis is multiple regression analysis (OLS), while hypothesis testing is carried out using the t-statistical test. Based on the results of hypothesis testing, it was found that the fraud triangle dimensions as measured by pressure, opportunity and rationalization had a positive effect on academic fraud committed by accounting students at the Faculty of Economics and Business, Padang State University, but misuse of information technology did not have a significant effect on academic fraud committed by accounting students. at the Faculty of Economics and Business, Padang State University